ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI - Selvi Diliyanti Rizki (Jurnal Manajemen, 2020)
This study aims to determine the behavior of Organizational Citizenship Behavior (OCB) on the employees of CV.Setia Damai Kendari. This research is a quantitative study, with the study population are employees of CV Setia Damai Kendari, amounting to 34 respondents who will be taken by census. The analytical tool used is quantitative descriptive analysis. Based on the results of the study found that Organizational Citizenship Behavior (OCB) for employees in the Office of CV. Setia Damai Kendari, on average, a value of 19.52. The magnitude of this value, indicates that employees in the Office of CV. Setia Damai Kendari has Organizational Citizenship Behavior (OCB) behavior. This indicates that employees at CV. Setia Damai Kendari has ethical behavior that refers to behavior to help colleagues, supervisors or organizations and includes actions such as helping coworkers, trying to improve morale, volunteering for work that is not part of the job description, talking positively about the organization to people as well as suggesting improvements in organizational functions. Organizational Behavior Citizenship Behavior (OCB) employees at the Office of CV. Faithful Damai Kendari, can not be separated from the role of each behavior that forms the behavior of OCB, namely: civic virtue (civic virtue), conscientiousness (conscience) and courtesy (courtesy) which in the result has been owned by employees. As for the other case for alruism (alruis) and sportmanship (sportsmanship) behavior which in the results indicate that employees at CV. Setia Damai Kendari does not yet have altruism and sportsmanship behavior. The low behavior of employees in terms of altruism and sportsmanship at the same time shows that employee behavior in the CV. Kendari Faithful Damai is more likely to